Літературна специфіка біографічної кіноповісті: до питання жанрової спадковості. - Matiychak, Aliona; Nikoriak, Natalia (Питання літературознавства, 2021)
The genre heredity concept is articulated on the analysis example of I. Drach’s screen version of the biographical film story “I’m coming to you” (1970), dedicated to the 100th anniversary of Lesya Ukrainka. The film is marked by innovative approach of I. Drach as a scriptwriter to the image of the poetess. Contrary to the tradition of documentary film to interpret her biography in a certain matrix key (as a fighter and revolutionary), Drach tried to identify Lesya Ukrainka primarily as a private individual, as the woman who knew how to sacrifice herself for the sake of love. Without aiming to show in detail the entire biography of the poetess, the author of the film story chose only a small fragment of her life – four years 1897–1901. In terms of biopic genre heredity, the article observes how this biographical film presents possible ways of processing and contamination of available documentary material (letters, memoirs, reminiscences of contemporaries) and integral creation by Lesya Ukrainka (her poetry, translations, renditions). Hence, the biopic on the basis of multi-genre text material appears as a kind of intertextual plexus. At the same time, the film pays much attention to the feelings, thoughts, creative impulses and state of mind of the heroine. By analogy with the poetics of literary writing, the form of the poetess’ inner monologue was chosen in accordance with the portrait film genre. It is clear that through the prism of Lesya’s life and creative experience the personal attitude of the poet I. Drach emerges towards understanding and reproducing the figure of creative personality in art: the author’ vision logically leads to those biographical episodes that in the existential sense appear the most significant.
Literary Specifics of Biographical Film Story: On the Issue of Genre Heredity
Keywords: genre heredity, biographical film story, biopic, existential situation